Teologi Kuliner Dalam Upaya Melaksanakan Misi GerejaGEREJA - Waruwu, Erlina; Gultom, Rogate Artaida Tiarasi; Damanik, Dapot (Jurnal Apokalupsis, 2025)
The contemporary church faces serious challenges in carrying out a mission that is relevant within Indonesia’s multicultural and multireligious society. Although missiological studies emphasize the importance of contextualization, church mission approaches still largely rely on verbal and institutional methods that inadequately engage the everyday practices of the community. Meanwhile, the practice of shared meals, which holds strong social and religious significance in Indonesian culture, has received limited theological attention as a strategy for church mission. This research gap highlights the lack of exploration of culinary theology as a missional bridge that connects Christian faith with the lived reality of communal life in public spaces. This study aims to examine how culinary theology can be developed as a contextual and grounded approach to church mission through the practice of shared meals rich in theological, social, and missiological meaning. Using a descriptive qualitative method with a literature study approach, this research draws on theological, missiological, and biblical sources. The findings indicate that culinary theology functions as an effective missional bridge by creating inclusive and relational spaces where the values of Christian love, hospitality, and solidarity are experienced concretely. Integrating culinary theology enriches contextual church mission and encourages the development of culinary-based ministries as a tangible expression of God’s mission in society